Overpressure preventing quartz cementation? - A reply. (January 2017) - Stricker, Stephan; Jones, Stuart J.; Sathar, Shanvas
Abstract: Chemical compaction and the relative importance of the pressure dissolution and illite-mica induced dissolution (IMID) models have remained a contentious issue, as is the role played by stress in chemical compaction. This paper offers further support and evidence as discussed in Stricker et al. (2016b), focusing on the reservoir quality of the Triassic Skagerrak Formation sandstones in the high pressure high temperature (HPHT) Central Graben, North Sea. The reply discusses alterative reservoir quality interpretations and comments as raised by Maast (2016). A series of theoretical and experimental studies, as well as field based evidence is presented providing strong support to the important role of stress (e.g. vertical effective stress) during chemical compaction. The evidence leads to the conclusion that the process of chemical compaction is stress and temperature driven and significantly enhanced by clay minerals, playing a catalytic role by increasing the width of diffusion pathway or by modifying the kinetics of the dissolution process.